2011
DOI: 10.1186/2043-9113-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Automated ERCC1 immunochemistry on hybrid cytology/tissue microarray of malignant effusions: evaluation of antibodies 8F1 and D-10

Abstract: BackgroundThe excision repair cross-complementation group 1 (ERCC1) protein is the key enzyme of the nucleotide excision repair (NER) pathway. Loss of protein expression on immunohistochemistry is predictive for platinum-based chemotherapy response. Frequently, the diagnosis of malignancy is made on cytologic effusion samples. Therefore, we evaluated the staining quality of monoclonal anti-ERCC1 antibodies 8F1 and D-10 on microarrays of malignant pleural and peritoneal effusions by automated immunochemistry.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Currently, there is no clinically approved ERCC1 IHC diagnostic assay available, likely due to the lack of a high quality anti-ERCC1 monoclonal antibody. Studies from a number of labs have shown that the 8F1 clone gives the best performance on NSCLC tissue in IHC assays [18,34]. However, Bhagwat, et al claimed that 8F1 is not mono-specific [19].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no clinically approved ERCC1 IHC diagnostic assay available, likely due to the lack of a high quality anti-ERCC1 monoclonal antibody. Studies from a number of labs have shown that the 8F1 clone gives the best performance on NSCLC tissue in IHC assays [18,34]. However, Bhagwat, et al claimed that 8F1 is not mono-specific [19].…”
Section: Discussionmentioning
confidence: 99%
“…The effusion liquids were prepared and processed as previously described [32]. Briefly, after low-speed centrifugation, the upper white phase of the sediment was aspirated and transferred into a micro tube.…”
Section: Preparation Of Cellblocks and Cytologic Microarray (C-tma)mentioning
confidence: 99%
“…As described previously ( 29 ), the effusion liquids were centrifuged and the sediments were transferred into a microtube. Subsequently, thrombin and plasma were added for clot formation.…”
Section: Methodsmentioning
confidence: 99%